Exploring the impact of IS function maturity and IS planning process on IS planning success: an ACE analysis. Issue 4 (4th July 2019) - Shimada, Tomoaki; Ang Soo-Keng, James; Ee, Darren
ABSTRACT: We examine the impact of information system (IS) function maturity and IS planning process on IS planning success in an exploratory approach. We conducted non-linear regression analysis using the Alternating Conditional Expectations algorithm, and found significant non-linear relationships between the dimensions of IS function maturity/IS planning process and those of IS planning success. We also visualised how various IS planning success measures can evolve with low or high values of determinant variables. We used four dimensions of capabilities, analysis, cooperation, and alignment to evaluate IS planning success. We also employed four dimensions to analyse each of IS function maturity and IS planning process. IS function maturity consists of IT planning mode, IT integration, IT industry practice, and IT perspective. On the other hand, IS planning process is composed of long-range planning, medium-range managerial planning, short-range operational planning, and organisational IT potential.